“Diseño de un sistema de control en la tolva de alimentación del primer molino de extracción de jugo de caña para mejorar la calidad de producción”. - Medina Palta, Johanna Marivel (2022)
Traditionally, in sugar mills there have been a series of processes involved, of which, in the cane juice extraction process, there are serious problems of discontinuity in the feeding of raw material in the conveyor belts of cane mills. The variable that is manipulated to control the level of cane is the speed of the motor that drives the cane conveyor and the speed of the mill. For the present investigation, the transfer function of the mill was modeled and the PID control was developed based on simulations in the Matlab software, once these simulations were tested, the tuning parameters of the multivariable control were taken and the PID control was programmed in the PLC implemented in the mill machinery, giving very encouraging results in terms of optimization of energy consumption. This work concluded the importance of implementing a control strategy in the first mill, since, although the production speed was not improved, energy consumption was reduced by 2.88%, which represents economic savings for the company, said savings have been achieved without an initial investment since it was only necessary to reprogram the mill controller together with the company's plant personnel.